INFLUENCE OF SPEED ELECTRON RADIATION ON THE PROPERTIES OF GALIUM ARSENID - Завадський, В. А.; Зубарєв, В. В.; Лєнков, С. В.; Тарієлашвілі, Г. Т. (Proceedings of National Aviation University (archive), 2021)
The results of experimental studies of the nature of the influence of fast electron irradiation on the main characteristics of gallium arsenide, one of the promising materials for onboard electronics, are presented.